CO2 capture in different carbon materials - Jiménez, Vicente; Ramírez-Lucas, Ana; Díaz, José Antonio; Sánchez, Paula; Romero, Amaya (Environmental science & technology, 2012)
In this work, the CO(2) capture capacity of different types of carbon nanofibers (platelet, fishbone, and ribbon) and amorphous carbon have been measured at 26 °C as at different pressures. The results showed that the more graphitic carbon materials adsorbed less CO(2) than more amorphous materials. Then, the aim was to improve the CO(2) adsorption capacity of the carbon materials by increasing the porosity during the chemical activation process. After chemical activation process, the amorphous carbon and platelet CNFs increased the CO(2) adsorption capacity 1.6 times, whereas fishbone and ribbon CNFs increased their CO(2) adsorption capacity 1.1 and 8.2 times, respectively. This increase of CO(2) adsorption capacity after chemical activation was due to an increase of BET surface area and pore volume in all carbon materials. Finally, the CO(2) adsorption isotherms showed that activated amorphous carbon exhibited the best CO(2) capture capacity with 72.0 wt % of CO(2) at 26 °C and 8 bar.